CIVIL JUSTICE IN INDIA - K. Agrawal; N. Dixit (BRICS Law Journal)
In India the concept of civil justice is not new. It has existed since time immemorial. A large number of related provisions are found in Manu, who compiled the then existing justice system in India of thousands of years ago in his fourteen-volume work titled Manava Dharma Shastra. The concept of justice is also found in detail in the Vedas, which are from avery ancient time. In both these scriptures the rule of law was adequately provided. Today, however, the Indian civil justice system resembles its common law counterparts. It features a coordinated, pyramid structure of judicial authority, emphasizing formal procedural justice dominated by litigants of equal status engaged in adversarial processes, and provides binding, win-lose remedies.